2019
DOI: 10.1371/journal.pone.0222606
|View full text |Cite
|
Sign up to set email alerts
|

Microliths in the South Asian rainforest ~45-4 ka: New insights from Fa-Hien Lena Cave, Sri Lanka

Abstract: Microliths–small, retouched, often-backed stone tools–are often interpreted to be the product of composite tools, including projectile weapons, and efficient hunting strategies by modern humans. In Europe and Africa these lithic toolkits are linked to hunting of medium- and large-sized game found in grassland or woodland settings, or as adaptations to risky environments during periods of climatic change. Here, we report on a recently excavated lithic assemblage from the Late Pleistocene cave site of Fa-Hien Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 97 publications
(155 reference statements)
2
28
0
1
Order By: Relevance
“…In a review of miniaturized industries across the world, Pargeter and Shea (2019) found that systematic blade production is a common but not universal feature, with blades providing the advantage of a relatively long, straight cutting edge on a small tool. In both India and Sri Lanka for example, miniaturization is a key feature of assemblages in the last 50 ka, but only in the former is there systematic blade production (Clarkson et al, 2018b;Clarkson et al, 2020;Lewis et al, 2014;Mishra et al, 2013;Perera, 2010;Petraglia et al, 2009;Wedage et al, 2019;Wedage et al, 2020). The evidence from Panga ya Saidi supports this close, but decoupled relationship, with systematic blade production an early yet intermittent feature of the miniaturized LSA sequence.…”
Section: The Middle To Later Stone Age Lithic Transition In Eastern A...mentioning
confidence: 89%
“…In a review of miniaturized industries across the world, Pargeter and Shea (2019) found that systematic blade production is a common but not universal feature, with blades providing the advantage of a relatively long, straight cutting edge on a small tool. In both India and Sri Lanka for example, miniaturization is a key feature of assemblages in the last 50 ka, but only in the former is there systematic blade production (Clarkson et al, 2018b;Clarkson et al, 2020;Lewis et al, 2014;Mishra et al, 2013;Perera, 2010;Petraglia et al, 2009;Wedage et al, 2019;Wedage et al, 2020). The evidence from Panga ya Saidi supports this close, but decoupled relationship, with systematic blade production an early yet intermittent feature of the miniaturized LSA sequence.…”
Section: The Middle To Later Stone Age Lithic Transition In Eastern A...mentioning
confidence: 89%
“…Alaska, it has been noted that recently deglaciated landscapes are productive new lands which were often exploited by small, highly mobile bands utilizing a miniaturized lithic technology with micro-blades [26][27][28][29][30][31]. While lithic miniaturization is a global phenomenon in the Early Holocene [32][33][34][35][36], the North American cases, including this new find from Lake Huron, seem particularly suited to the habitation of new lands exposed during glacial retreat. It is tempting to view the long-distance…”
Section: Plos Onementioning
confidence: 99%
“…In conclusion, the present results open a debate on the impact of demic diffusion on the very origin of the Late Epigravettian material culture and the mechanisms underlying patterns recorded before and after the onset of the Bølling/Allerød event. These include the later convergent emergence across Eurasia of a more flexible and responsive technology, and of schematic art 40 associated with change in demographic pressure, environmental challenges, and mobility [41][42][43] .…”
Section: Discontinuity Between Early Epigravettian and Late Epigravetmentioning
confidence: 99%